Penerapan Terapi Uap Air Panas dan Minyak Kayu Putih pada Anak Bronkopneumonia di Charitas Hospital Belitang - Eka Rusmini; Maria Tarisia Rini; Ketut Suryani (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Excessive mucus or secretions in the lungs are a common symptom of bronchopneumonia in children. The buildup of thick phlegm will be difficult to expel and can block the child's respiratory tract. One way to relieve a blocked nose and thin phlegm is by mixing eucalyptus oil and hot water. The ability of eucalyptus oil to break down mucus is caused by cineole. The nursing student's final goal is to present a research synopsis on the use of hot steam therapy along with eucalyptus oil to clear the airways of ineffective bronchopneumonia in children. Using a case study design with three (3) respondents and a mixture of hot water steam and eucalyptus oil, this research uses case study techniques and a nursing process approach. Children aged between three and four years can benefit greatly from a treatment that involves inhaling eucalyptus oil vapors for ten to fifteen minutes to clear the respiratory tract and reduce the viscosity of mucus. The results of implementing the intervention showed that the average results for respondents were 1,2,3 pre-intervention, SpO2 98%, RR: 31x/m, rhonchi(-) R1:30, R2:30, R3:32. post intervention results showed SpO2: 99% and HR: 24x/m, R1:24, R2:25, R3:24. The combined intervention of hot water steam with eucalyptus oil is effective in reducing respiratory frequency in children with bronchopneumonia.